THE EFFECTIVENESS OF LOCAL COMMUNITY-BASED EMPOWERMENT LEARNING IN IMPROVING STUDENTS’ CRITICAL AND CREATIVE THINKING: A CASE STUDY IN SMAN 2 CIANJUR - Fani Julia Putri (FKIP ULM, 2017)
Abstract: The formulations of the problems and the purposes of this research were about the learning process of empowerment of local communities and the impact of learning about local community in improving critical and creative thinking of students at SMAN 2 Cianjur. Data and information collection techniques used were the interview, observation, and record of the experience. The findings of this study were: (1) The students of SMAN 2 Cianjur conducted three stages of empowerment, namely the planning stage by dividing the class into nine groups of experts along with their respective duties, the implementation stage consisting of the presentation and demonstration of the student’s innovations, and the last one, that is, the assessment stage carried out by various assessors. (2) local community-based empowerment was considered to be appropriate to increase students' critical and creative thinking. Then, the publication by students was also as a concrete action that through the use of electronics we can improve the productivity and the marketing of the local communities in order to remain sustainable and adaptive in accordance with the current developments. Keywords: critical and creative thinking, empowerment, local community Abstrak. Rumusan masalah dan tujuan penelitian ini adalah tentang proses pembelajaran pemberdayaan masyarakat lokal dan dampak pembelajaran masyarakat lokal dalam meningkatkan berpikir kritis dan kreatif siswa SMAN 2 Cianjur. Teknik pengumpulan data dan informasi menggunakan wawancara, observasi, dan catatan pengalaman. Temuan penelitian ini adalah: (1) Siswa SMAN 2 Cianjur melaksanakan tiga tahap proses pemberdayaan masyarakat, yaitu tahap perencanaan dengan membagi kelas menjadi sembilan kelompok ahli beserta tugasnya masing-masing, tahap pelaksanaan yang terdiri dari presentasi dan demonstrasi inovasi siswa, dan yang terakhir, yaitu tahap penilaian yang dilakukan oleh berbagai penilai. (2) Pemberdayaan masyarakat berbasis lokal dianggap tepat untuk meningkatkan pemikiran kritis dan kreatif siswa. Selain itu, publikasi yang dilakukan oleh siswa juga merupakan tindakan nyata, di mana melalui penggunaan media elektronik produktivitas dan pengenalan terhadap masyarakat lokal dapat ditingkatkan untuk menjaga agar tetap lestari dan adaptif sesuai dengan perkembangan saat ini. Kata Kunci: berpikir kritis dan kreatif, pemberdayaan, masyarakat lokal